2022
DOI: 10.1161/circoutcomes.121.007923
|View full text |Cite|
|
Sign up to set email alerts
|

Efficacy and Safety of Chinese Herbal Medicine Compared With Losartan for Mild Essential Hypertension: A Randomized, Multicenter, Double-Blind, Noninferiority Trial

Abstract: Background: Hypertension is one of the most challenging public health problems worldwide. Previous studies suggested that the Songling Xuemaikang capsule (SXC)—a Chinese herbal formula—was effective for essential hypertension. However, the efficacy of SXC monotherapy for hypertension remains unclear. We aimed to compare the blood pressure (BP)–lowering efficacy and safety of SXC versus losartan in patients with essential hypertension. Methods: In this m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 46 publications
0
18
0
Order By: Relevance
“…4 In studies of the efficacy of natural products and losartan, Lai et al 12 evaluated a traditional Chinese natural product remedy in a large cohort of patients (over 1000 patients in all) with mild to moderate hypertension, who were taking either the traditoonl Chinese Medicine (TCM) or the losartan regimen and found the outcomes to be equivalent to those of a daily 50mg dosage of losartan in controlling both systolic and diastolic pressure. 19 In another study by conducted by Chow et al 20 the authors also reported a similar outcome success when comparing a traditional ancient TCM regimen (the THSWT or SWT described above) to allopathic medications in patients with mild to moderate hypertension, and TulIp et al reported a case study that demonstrated the efficacy of mango leaf tea as monotherapy in controlling markers of mild to moderate hypertension in Montserrat in the absence of availability allopathic medications, and where the consumption of locally-prepared mango leaf tea is common. 4,20 In the present case studies reviewed above, it became apparent that the single daily dosage of the allopathic medication combination was inadequate to provide effective 24-hr control of blood pressure measurements, with the effectiveness of the regimen beginning to wane within 4 to 6hours after morning drug administration, suggestive of early drug clearance, multidrug resistance, or some combination of the two factors.…”
Section: Discussionmentioning
confidence: 99%
“…4 In studies of the efficacy of natural products and losartan, Lai et al 12 evaluated a traditional Chinese natural product remedy in a large cohort of patients (over 1000 patients in all) with mild to moderate hypertension, who were taking either the traditoonl Chinese Medicine (TCM) or the losartan regimen and found the outcomes to be equivalent to those of a daily 50mg dosage of losartan in controlling both systolic and diastolic pressure. 19 In another study by conducted by Chow et al 20 the authors also reported a similar outcome success when comparing a traditional ancient TCM regimen (the THSWT or SWT described above) to allopathic medications in patients with mild to moderate hypertension, and TulIp et al reported a case study that demonstrated the efficacy of mango leaf tea as monotherapy in controlling markers of mild to moderate hypertension in Montserrat in the absence of availability allopathic medications, and where the consumption of locally-prepared mango leaf tea is common. 4,20 In the present case studies reviewed above, it became apparent that the single daily dosage of the allopathic medication combination was inadequate to provide effective 24-hr control of blood pressure measurements, with the effectiveness of the regimen beginning to wane within 4 to 6hours after morning drug administration, suggestive of early drug clearance, multidrug resistance, or some combination of the two factors.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with Western medicine, Chinese herbal medicine has the advantages of multi-channel and multi-target comprehensive intervention in blood pressure reduction. It has the characteristics of exible addition and subtraction, individualization, and relatively less toxic side effects in long-term medication [21,22]. Therefore, it is signi cant to strengthen the exploration of Chinese herbal medicine in treating hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study using animal models showed that SXC inhibits renin-angiotensin-aldosterone system, 7 which is the mechanism of ACE (angiotensin-converting enzyme) inhibitors and angiotensin receptor blockers to lower BP. Lai et al 6 proved that SXC also had a similar safety profile as losartan. These promising findings indicate that SXC has the potential to replace losartan or other ACE inhibitors/angiotensin receptor blockers in treating mild essential hypertension, rather than merely acting as complementary medicine.…”
Section: See Article By Gao Et Almentioning
confidence: 99%
“…In this issue, Lai et al 6 reported the results of a multicenter, randomized, double-blind trial, which included 628 patients with mild essential hypertension (systolic BP 140-159 mm Hg and/or diastolic BP 90-99 mm Hg) and without preexisting cardiovascular diseases or uncontrolled diabetes. The trial demonstrated that a Chinese herbal patent formula, Songling Xuemaikang Capsules (SXC), was noninferior to losartan in reducing office diastolic BP after an 8-week treatment.…”
Section: See Article By Gao Et Almentioning
confidence: 99%